Analisis Peran Kegiatan Melukis terhadap Anak Berkebutuhan Khusus di Sentra Terpadu Prof. Dr. Soeharso Surakarta - Slamet Supriyadi; Videlis Mutiara (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Children with Special Needs (CSN) have unique potential that requires special approaches to support their development. This study aims to analyze the role of painting activities in the development of fine motor skills, concentration, emotional regulation, and self-expression of CSN at the Integrated Center Prof. Dr. Soeharso Surakarta. Using a descriptive-qualitative method, data were collected through interviews, observations, and documentation. Data analysis was carried out using Miles and Huberman's interactive techniques, including data reduction, data presentation, and conclusion drawing. The results showed that painting activities effectively train fine motor skills through the use of brushes, enhance concentration and emotional regulation abilities, and provide a platform for self-expression for CSN. Moreover, painting helps boost children’s self-confidence through the appreciation of their artwork. These findings emphasize the importance of painting as part of an educational and therapeutic approach to support CSN development. Its implication is that painting can be more broadly implemented in inclusive educational activities to strengthen children’s abilities in various aspects of development.